Catatan untuk Maksimisasi Keuntungan: Sebuah Pertanyaan yang Ditujukan Kepada Prinsip “MC=MR” - Munrokhim Misanam (Universitas Islam Indonesia, 2007)
It has long been set that the condition for maximum profit is MC=MR. Moreover, this condition has been one of doctrines in microeconomics for decades since Professor Marshall changed the name of the area from Political Economy to be Economics. The condition is mathematically derived from the process of profit maximization. This article is trying to ask whether the condition is valid for every situation. There is one hole that makes this condition seems weird, that is, in the case of unitary elastic and inelastic demand. In the first case the condition dictates that the producer should take infinity mark-up, while in the second case the condition commands to make a negative mark-up which is of course unreasonable in either way. This article also explores the possible argument for this condition, which is linear demand curve. Still, this argument cannot cover the entire cases. Furthermore, this article argues that the demand producers always face is either non linear or constant-elasticity in nature. The imperfection of the condition stems from the fact that it fails to impose second order (sufficient) condition when maximizing profit. This article is trying to explore the assumption-free condition by imposing second order (sufficient) condition. The result even though a bit complex in its expression but it gives a strong implication.Keywords: MC, MR, profit maximization